Guidance and Counselling: Its Impact and Services in Tertiary Institutions in Borno State, Nigeria - Yagana Alkali Kolo; Bitrus Glawala Amuda (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
The study evaluated the Impact of Guidance and Counselling Services in Tertiary Institutions in Borno State, Nigeria. The study used survey design. One objective was formulated and one research question was raised. The population of the study consisted of all tertiary institutions in Borno State. However, the study was delimited to 4 tertiary institutions with established guidance and counselling centers. The total number of students and counsellors used in the study was 1,237 students and 4 counsellors selected through simple random and purposive sampling techniques. The instrument used was self-developed questionnaire titled the Impact of Guidance and Counselling Services (IGCSQ) consisted of 12-items instrument. The reliability co-efficient of the instrument was determined after pilot testing was conducted and the index was found to be 0.80 using Cronbach’s alpha. One hypothesis tested at 0.05, level of significance guided the study. The hypothesis revealed that there was no significant difference on the impact of Guidance and counselling services in all the tertiary institutions. Frequencies, percentages, mean and standard deviation were employed to answer the research questions. The result showed that the impact of guidance and counselling on orientation, information, counselling, planning placement and follow-up services have high impact. The study concluded that there was a high impact on all the guidance services. Based on the findings the study recommended that National Universities Commission (NUC) and National Commission for Colleges of Education (NCCE) should organize periodical evaluation of all the guidance and counselling services in order to ensure its effectiveness on students in all the tertiary institutions.